ANALISIS KEMAMPUAN BERPIKIR SISWA KELAS VIII PADA MATERI ZAT ADIKTIF DAN ADITIF - Shafiyah, Amirah Nur; Sabtiawan, Wahyu Budi (Universitas Negeri Surabaya, 2024)
The study aimed to analyze the critical thinking abilities of eighth grade students on substance addictions and addictive substances. The analysis of critical thinking capabilities in this study was modified using Ennis indicators such as simple explanations, basic skills, conclusions, further explanations, as well as strategies and tactics. This type of research is descriptive-quantitative. The research subjects used were all the students in the eighth grade of high school. The instrument used in this study is a critical thinking description test. Data collection techniques using test techniques. The data analysis technique used is a calculation of averages that are described based on the results of the calculation. The results of this study showed that the highest percentage score of critical thinking ability was in class D at 17% with an average of 16.26, while the lowest percentual score of critical thinking was in class A at 13% with an average of 11.91.